2012
DOI: 10.1159/000337956
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of the Blood Component Utilization in a University Hospital of Maximum Medical Care

Abstract: Background: Demographic data illustrate clearly that people in highly developed countries get older, and the elderly need more blood transfusions than younger patients. Additionally, special extensive therapies result in an increased consumption of blood components. Beyond that the aging of the population reduces the total number of preferably young and healthy blood donors. Therefore, Patient Blood Management will become more and more important in order to secure an increasing blood supply under fair-minded c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 23 publications
3
18
0
1
Order By: Relevance
“…The data obtained in our retrospective analysis are in agreement with previously published results concerning the overall blood consumption of RBC, FFP and PLT units in cardiac surgery [1,2,3,4,5,6,13]. The percentage of patients requiring RBC, FFP or PLT units noticeably decreased after the introduction of the PBM measures in January 1, 2012, whereas significantly more blood (RBCs) per patient was provided in 2012 (7,253 RBC units) compared to 2009 (5,998 RBC units), which might reflect the above mentioned complexity factor.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The data obtained in our retrospective analysis are in agreement with previously published results concerning the overall blood consumption of RBC, FFP and PLT units in cardiac surgery [1,2,3,4,5,6,13]. The percentage of patients requiring RBC, FFP or PLT units noticeably decreased after the introduction of the PBM measures in January 1, 2012, whereas significantly more blood (RBCs) per patient was provided in 2012 (7,253 RBC units) compared to 2009 (5,998 RBC units), which might reflect the above mentioned complexity factor.…”
Section: Discussionsupporting
confidence: 92%
“…In many hospitals that provide comprehensive medical care, the usage of blood components during cardiac surgery is much greater than the average blood product demand in most other medical disciplines [1,2,3,4,5,6]. Today, blood transfusions have become more and more accepted as a major quality indicator in cardiac surgery [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hemato-oncological patients comprised 37.1% of all cases and received 50.9% of transfused units of PCs [27]. A study on PC use in the North of England in 2012 showed similarly that 60.5% of PC transfusions were given to hemato-oncological patients.…”
Section: Major Use Of Platelet Transfusions In Hemato-oncological Patmentioning
confidence: 99%